Lonely planet great britain - Else, David; Bainbridge, James; Berry, Oliver; Davenport, Fionn; Dixon, Belinda; Atkinson, David; Luckham, Nana.; Symington, Andy.; Wilson, Neil.; O'Carroll, Etain ([S.l.] : Lonely Planet, 2009)
Nobody knows Great Britain like Lonely Planet. Whether you're after prehistoric sites in Orkney, mountain climbing in Snowdonia, the tastiest fish and chips in East Anglia, or a quiet beach in Cornwall, this 8th edition gives you all the information you need to enjoy the best of Britain. Lonely Planet guides are written by experts who get to the heart of every destination they visit. This fully updated edition is packed with accurate, practical and honest advice, designed to give you the information you need to make the most of your trip. In This Guide: Top insider tips from a celebrity chef, the King of Hay and a ghost-tour guide Detailed itineraries help you discover the highlights of Britain Unique Green Index picking out the top sustainable travel options.